تحسين مؤشري السرية والثباتية عند تصميم شبكات الاتصال الراديوي - احمد علي (Latakia University Journal -Engineering Sciences Series, 2019)
في البحث التالي تم دراسة تحليل وتركيب شبكات الاتصال الراديوي بمؤشرات السرية والثباتية (الحماية من التشويش والحيوية) بحيث يتم فك الارتباط بين الشبكة كبنية ووظيفة وبالتالي إلغاء القرائن الدالة المنظومية للشبكات وهذا ما يصعب عملية التعرف على الشبكة وأهمية مستخدميها ويعطي الشبكة نوعا من المرونة بالمؤشرات السابقة وخاصة بعد استخدام الوسائط المناسبة التي تسمح بتحقيق النتائج التي تم الحصول عليها ومن هذه الوسائط أجهزة الإرسال الباكيتي ذات التامين البرمجي وأجهزة الإرسال بالطيف المنثور(قفز ترددي مع سلسلة عشوائية). في البحث تم تحليل الخوارزميات المستخدمة في تصميم الشبكات وإظهار سلبياتها وإيجابياتها والوصول إلى نتائج ذات وثوقية عالية. This research deals with providing radio communication networks with stability and security factors (protection from interference). In so doing, we deconstruct the link between the structure and function of the network, thus invalidating the systemic indicative presumptions of the networks. This will make the process of identifying the network and the importance of its users very difficult, giving the network some flexibility by the previous factors, especially after using the appropriate means which permit achieving the desired results. Of these means are transmission devices equipped with secure programming and transmission devices by diffuse spectrum. The algorithm used in network design has been analyzed, highlighting its strengths and weaknesses, obtaining results of high reliability.